PRAKTIK EARNING MANAGEMENT DALAM PERSPEKTIF ETIKA SYARI’AH - Hafni, Diska Arliena (Journal of Innovation in Business and Economics, 2012)
Earning Management representing one of choice to manager in determining policy of accountancy to reach specific purposes. The target is to maximize manager utilitas and improve company value. This target relate manager motivation in earning management praktik as: getting high bonus, debt in bond fund, trust of public in capital market, low tax expense, achievement which both for CEO , and positive reaction of investor in IPO. With existence of the target of profit management to maximize utilitas, hence profit management activity can be classified into ethics understanding of utilitarianisme. But which still become question in earning management will delivering many benefit to management  agent or principle, particularly all stakeholder.